Passivity and passification of switched systems with the persistent dwell time switching. (November 2019) - Zhao, Xiao-Qi; Ye, Dan; Zhong, Guang-Xin
Abstract: This paper addresses passivity and passification of discrete-time switched systems. New passivity conditions are established for switched systems with a designed switching strategy and output feedback controllers. The switching strategy refers to a more general persistent dwell time (PDT) switching approach, which includes the advantages of dwell time and arbitrary switching. Further, by introducing a time-dependent storage function, a non-weighted passivity index is guaranteed, which replaces the common weighted one under the average dwell time switching. Next, on the basis of a time-varying parameter describing the process of dwell time and arbitrary switching, output feedback controllers with time-varying gain are determined. This guarantees the passivity of closed-loop systems. Thus, the problem of passification under the PDT switching is solved. Finally, a verification example is provided to show the feasibility of the theoretical results.